Kecerdasan Emosional Dan Karakter Santun Siswa Sekolah Dasar: Studi Kolerasi - Vina Jazimatul Chusna; Hamidulloh Ibda; Effi Wahyuningsih (Inovasi-Jurnal Diklat Keagamaan, 2022)
The moral and mental degradation of students indicates low emotional intelligence in various countries, including Indonesia, with indicators of loss of manners, bad language, bullying, brawling, etc. This study aimed to determine the influence of students’ emotional intelligence levels on the manners character of 5th-grade students of Madrasah Ibtidaiyah al-Islam Balesari, Magelang, Indonesia. The study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. Sampling was done by a random sampling technique with a purposive sampling type. Data were collected through observation, questionnaires, and documentation with simple linear regression analysis assisted by SPSS 16 software for Windows. The results show that the average value of emotional intelligence in the experimental class is 79.4% (high-level category), while the control class is 72% (medium-level). On the other hand, the character of manners in the experimental class is 79% (very good category), and in the control class is 72% (sufficient category). The results indicate that there is an influence of students’ emotional intelligence on their manners and characters. The results of a simple regression test in the experimental class are Y = 11.354.–0.861 with a significant value of 0.00. The significance value is <0.05 (0.00<0.05), then Ha is accepted and Ho is rejected. The results of a simple regression test in the control class are Y = 17,323- 0.760 with a significant value of 0.00, the significance value <0.05 (0.00 <0.05), then Ha is accepted and Ho is rejected. The research findings concluded that the higher the level of emotional intelligence, the higher the manners of character, and vice versa. Further research needs to be conducted to explore the influence of emotional intelligence on the students’ character as a whole